Synergistic Encapsulation of Paclitaxel and Sorafenib by Methoxy Poly(Ethylene Glycol)-b-Poly(Caprolactone) Polymeric Micelles for Ovarian Cancer Therapy - Chae Eun Jin; Moon Sup Yoon; Min Jeong Jo; Seo Yeon Kim; Jae Min Lee; Su Jeong Kang; Chun-Woong Park; Jin-Seok Kim; Dae Hwan Shin (MDPI AG, 2023)
Ovarian cancer has a high mortality rate due to difficult detection at an early stage. It is necessary to develop a novel anticancer treatment that demonstrates improved efficacy while reducing toxicity. Here, using the freeze-drying method, micelles encapsulating paclitaxel (PTX) and sorafenib (SRF) with various polymers were prepared, and the optimal polymer (mPEG-b-PCL) was selected by measuring drug loading (%), encapsulation efficiency (%), particle size, polydispersity index, and zeta potential. The final formulation was selected based on a molar ratio (PTX:SRF = 1:2.3) with synergistic effects on two ovarian cancer cell lines (SKOV3-red-fluc, HeyA8). In the in vitro release assay, PTX/SRF micelles showed a slower release than PTX and SRF single micelles. In pharmacokinetic evaluation, PTX/SRF micelles showed improved bioavailability compared to PTX/SRF solution. In in vivo toxicity assays, no significant differences were observed in body weight between the micellar formulation and the control group. The anticancer effect of PTX/SRF combination therapy was improved compared to the use of a single drug. In the xenografted BALB/c mouse model, the tumor growth inhibition rate of PTX/SRF micelles was 90.44%. Accordingly, PTX/SRF micelles showed improved anticancer effects compared to single-drug therapy in ovarian cancer (SKOV3-red-fluc).